Diabetic nephropathy and myocardial lesions in children with type 1 diabetes mellitus - Larisa Vasil'evna Kazakova; Elena Fedorovna Lukushkina; Leonid Grigor'evich Strongin; Elena Alexandrovna Azova (Сахарный диабет)
Aim. To elucidate the role of diabetic nephropathy in pathogenesis of myo-cardial lesions in children with type 1 diabetes mellitus from the results of dopplerography of intrarenal vessels. Materials and methods. The study involved 39 children with DM1 (mean age 12,5?2,6) divided into 2 groups. Group 1 included 12 patients with subclinical diabetic lesions in the kidneys (hyperfiltration), group 2 and 3 comprised 21 and 6 patients with diabetic neph-ropathy (microalbuminuria 30?300 mg/day or proteinuria respectively). All patients under-went standard examination to evaluate cardiovascular and vegetative nervous function. Analysis of spectrograms obtained by dopplerography of intrarenal vessels included main renal artery (MRA), segmental (SA), interlobe (ILA), arch (AA), and interlobular (ILbA) arteries. Results. The study groups were not significantly different in terms of MRA, SA, AA, and ILA hemodynamics but, unlike healthy controls, showed a nonlinear decreasing gradient in vascular resistance from MRA toward peripheral vessels especially ILA and AA. Left ven-tricular hypertrophy with disturbed diastolic performance documented in 64% of the patients correlated with microalbuminuria (r=0,56, p